Collaborative Innovation in Sustainable Educational Tourism Development in Pasawahan Village - Hadita, Akmala; Raesalat, Riksa; Hamidah, Nida; Rashid, Salman (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
The development of beekeeping edutourism in Pasawahan Village represents an innovative strategy to support rural economic growth while enhancing public awareness of bee ecosystems. This study analyzes the collaborative strategies underpinning this initiative using the Tourism Area Life Cycle (TALC) approach. Employing a descriptive qualitative method, data were collected through in-depth interviews, direct observation, and document analysis.The findings reveal that the development of beekeeping edutourism is driven by multi-stakeholder collaboration involving the village government, BUMDes, Petani Muda Perlebah Foundation, PT PLN (Persero) through its CSR program, and active community participation. This collaboration has been implemented through infrastructure development, technical capacity-building for local residents, and the adoption of digital marketing strategies to enhance tourist attraction and accessibility. Based on the TALC model, Pasawahan’s beekeeping edutourism is currently transitioning from the development stage toward consolidation. This phase is characterized by increasing visitor numbers and the diversification of tourism products and educational services. However, several challenges persist, including a shortage of skilled beekeeping experts, the absence of clear village-level tourism regulations, and suboptimal promotion and ticketing systems.To address these constraints, the study recommends strengthening community-based technical training, formulating village regulations to support sustainable tourism management, and enhancing integrated digital marketing and visitor management systems. With targeted and sustained collaboration, beekeeping edutourism has strong potential to emerge as a leading model of sustainable educational tourism. This study contributes novel insights by examining collaborative innovation in transforming a former sand-mining area into a sustainable edutourism destination in a rural Indonesian context, offering a practical framework for similar initiatives in developing countries. Keywords: beekeeping edu-tourism, collaborative strategy, tourism area life cycle, sustainable rural tourism, community-based tourism development